Balancing of B6 Vitamers Is Essential for Plant Development and Metabolism in Arabidopsis. Issue 2 (8th February 2016) - Colinas, Maite; Eisenhut, Marion; Tohge, Takayuki; Pesquera, Marta; Fernie, Alisdair R.; Weber, Andreas P.M.; Fitzpatrick, Teresa B.
Abstract : Manipulating the levels of the vitamin B6 salvage enzyme PDX3 reveals that alterations in vitamin B6 homeostasis and nitrogen metabolism are linked. Abstract: Vitamin B6 comprises a family of compounds that is essential for all organisms, most notable among which is the cofactor pyridoxal 5′-phosphate (PLP ). Other forms of vitamin B6 include pyridoxamine 5′-phosphate (PMP ), pyridoxine 5′-phosphate (PNP ), and the corresponding nonphosphorylated derivatives. While plants can biosynthesize PLP de novo, they also have salvage pathways that serve to interconvert the different vitamers. The selective contribution of these various pathways to cellular vitamin B6 homeostasis in plants is not fully understood. Although biosynthesis de novo has been extensively characterized, the salvage pathways have received comparatively little attention in plants. Here, we show that the PMP /PNP oxidase PDX3 is essential for balancing B6 vitamer levels in Arabidopsis thaliana . In the absence of PDX3, growth and development are impaired and the metabolite profile is altered. Surprisingly, RNA sequencing reveals strong induction of stress-related genes in pdx3, particularly those associated with biotic stress that coincides with an increase in salicylic acid levels. Intriguingly, exogenous ammonium rescues the growth and developmental phenotype in line with a severe reduction in nitrate reductase activity that may be due to the overaccumulation of PMP in pdx3 . Our analyses demonstrate an important link between vitamin B6 homeostasis and nitrogen metabolism.